Denying Assisted Dying Where Death is Not ‘Reasonably Foreseeable’: Intolerable Overgeneralization in Canadian End-of-Life Law - Reel, Kevin (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
The recent change in Canadian law to allow access to medical assistance in dying restricts eligibility, among its other criteria, to those for whom “natural death has become reasonably foreseeable.” A recent review of certain aspects of the law examined the evidence pertaining to extending access to assisted dying in three particular request situations currently denied: requests by mature minors, advance requests, and requests where mental illness is the sole underlying medical condition [1]. The requirement for this review was included in the legislation that introduced medical assistance in dying in Canada. Both the original change in the law and the review itself neglected to consider those with intolerable suffering for whom natural death is not reasonably foreseeable. This paper explores the possibility that access to assisted dying should be extended by removing this limiting criterion. It also considers the ethical challenges this might present for those who work in rehabilitation.